2016
DOI: 10.1093/femsec/fiw194
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophytes for sustainable crop production

Abstract: This minireview highlights the importance of endophytic fungi for sustainable agriculture and horticulture production. Fungal endophytes play a key role in habitat adaptation of plants resulting in improved plant performance and plant protection against biotic and abiotic stresses. They encode a vast variety of novel secondary metabolites including volatile organic compounds. In addition to protecting plants against pathogens and pests, selected fungal endophytes have been used to remove animal toxicities asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
190
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(201 citation statements)
references
References 146 publications
3
190
0
8
Order By: Relevance
“…It should be noted that strains FZB42 28 and SQR9 29 of the Gram-positive biocontrol bacterium Bacillus amyloliquefaciens are also sources of many antibiotics, such as fengycins, iturins, and surfactins 28, 29 . Also, many fungi produce antibiotics, which can be active against bacterial and/or fungal plant root pathogens 15, 30, 31 .…”
Section: War In the Rhizospherementioning
confidence: 99%
“…It should be noted that strains FZB42 28 and SQR9 29 of the Gram-positive biocontrol bacterium Bacillus amyloliquefaciens are also sources of many antibiotics, such as fengycins, iturins, and surfactins 28, 29 . Also, many fungi produce antibiotics, which can be active against bacterial and/or fungal plant root pathogens 15, 30, 31 .…”
Section: War In the Rhizospherementioning
confidence: 99%
“…can inhibit the cucumber Fusarium wilt 30 days after inoculation and some strains giving 20–79% control efficacy (Hong et al, 2007). As reported in recent studies, endophytic fungi can successfully suppress the fungal plant pathogens through various means including the promotion of plant growth and by induced resistance to the plants (Lugtenberg et al, 2016; Ownley et al, 2010; Youssef et al, 2016). Meanwhile, we cannot rule out other mechanisms, as some Trichoderma spp.…”
Section: Discussionmentioning
confidence: 98%
“…It has been repeatedly reported that endophytic fungi can be successfully used to protect plants against pests and diseases as these fungi producing protective metabolites, inducing resistance to the host plants to biotic and a biotic stress by improving their growth and by this directly or indirectly enhanced production and yield (Arnold et al, 2001; Kaul et al, 2012; Rai et al, 2014). These kinds of fungi hold massive potential for the development of eco-friendly and economically viable agricultural products (Lugtenberg et al, 2016). Endophytic fungi interact with their host plants in different ways, with each interaction giving rise to different alterations in both partners.…”
mentioning
confidence: 99%
“…Symbiotic interaction between plant and microbes considerably influences the development of plant and its metabolic processes (Rodriguez et al 2009;Jia et al 2016). Significant improvement in secondary metabolite biosynthesis and growth of the plant has been found to be associated with plant-endophyte interaction (Lugtenberg et al 2016). Endophytes reside in the inter-and intra-cellular spaces of a plant without causing any apparent harm to the plant (Lodewyckx et al 2002;Ryan et al 2008).…”
Section: Introductionmentioning
confidence: 99%